Anisotropy of CoII transferred to the Cr7Co polymetallic cluster via strong exchange interactions. Issue 14 (14th March 2018) - Garlatti, Elena; Guidi, Tatiana; Chiesa, Alessandro; Ansbro, Simon; Baker, Michael L.; Ollivier, Jacques; Mutka, Hannu; Timco, Grigore A.; Vitorica-Yrezabal, Inigo; Pavarini, Eva; Santini, Paolo; Amoretti, Giuseppe; et al.
Abstract : In the Cr7 Co model-system the anisotropy of Co II is effectively transferred to the whole cluster through strong and anisotropic exchange interactions. Abstract : The Cr7 Co ring represents a model system to understand how the anisotropy of a Co II ion is transferred to the effective anisotropy of a polymetallic cluster by strong exchange interactions. Combining sizeable anisotropy with exchange interactions is an important point in the understanding and design of new anisotropic molecular nanomagnets addressing fundamental and applicative issues. By combining electron paramagnetic resonance and inelastic neutron scattering measurements with spin Hamiltonian and ab initio calculations, we have investigated in detail the anisotropy of the Co II ion embedded in the antiferromagnetic ring. Our results demonstrate a strong and anisotropic exchange interaction between the Co and the neighbouring Cr ions, which effectively transmits the anisotropy to the whole molecule.